Giving Effect Trichoderma sp. In Tomato Plant To Production Factors - Sopialena Sopialena (Universitas 17 Agustus 1945 Samarinda, 2018)
Research on the effect of Trichoderma sp. In tomato plants on the factors of production is a study carried out for 4 months starting from June to October 2017. The research was carried out at the Green House of the Faculty of Agriculture, Mulawarman University, Samarinda.This research was conducted using a completely randomized design (CRD) with each treatment repeated 3 times. The treatment is Po: Without Trichoderma sp. / Control treatment; P1: 25 g culture of Trichoderma sp. per polybag; P2: 30 g of mushroom culture Trichoderma sp. per polybag; P3: 35 g of mushroom culture Trichoderma sp. Per polybag; and P4: 40 g culture of Trichoderma sp. per polybag As the second factor, tomato varieties include V1: Lentana; V2: Permata and V3: Ratna. The data observed included the number of planting fruit (calculated from the first harvest to the last harvest for each crop); Average diameter of planting fruit and. The average weight of fresh fruit plantations.The results showed that the dose of 40g Trichoderma sp. most effective in controlling F. oxysporum wilt disease on tomato plants, which can increase tomato crop production by 293.48 g. Variety treatment was not significantly different from all treatments. So that there is no interaction between Trichoderma sp. and tomato varieties.